Legal Reasoning Behind the Abolition of the Right to File for Judicial Review of Administrative Court Decisions by Administrative Agencies or Officials - Haru Permadi; Oppy Pramudya W. W. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of writing this article is to examine the legal reasoning for the elimination of the right to review the decision of a state administrative dispute by a state administrative body or official. The method used in writing this article is normative juridical. The study found that the Constitutional Court judges used a historical approach, a conceptual approach, and systematic interpretation in determining the abolition of the right of review in state administrative disputes by state administrative bodies or officials. In conclusion, the judges of the Constitutional Court abolished the right of judicial review to provide legal certainty over an inkracht decision of the State Administrative Court, protect public rights, and realize the original purpose of establishing the State Administrative Court.